"DAK", a traditional decoction in Palau, as adjuvant for patients with insufficient control of diabetes mellitus type II. (9th June 2017) - Kitalong, Christopher; Nogueira, Renata Campos; Benichou, Jeanne; Yano, Victor; Espangel, Vanessa; Houriet, Joëlle; Rudigier, Carla; Graz, Bertrand
Abstract: Ethnopharmacological relevance: Can a medicinal plant be useful when standard modern treatment is insufficient? After a population survey in the Republic of Palau (retrospective treatment-outcome study, following the reverse pharmacology approach) on local treatments and associated outcomes for diabetes, a traditional drink made with Phaleria nisidai Kaneh and several other plants called " Delal A Kar ", (meaning "mother of medicine") appeared as a promising therapy. This is the first clinical study on a standardized version of "Delal A Kar" called DAK . Aims/hypothesis: This is a study of the effect of DAK as adjuvant therapy when diabetes control is insufficient. Methods: In this randomized, double blind, crossover study conducted in Koror, Palau, DAK or placebo was assigned to 68 patients with type II diabetes treated with oral hypoglycemic agents and with insufficient glycaemic control. All patients received instructions on how to improve their diet and a home glucometer for blood glucose follow-up. Results: Fifty-five patients completed the study and significant improvements were observed in both groups over the 12 weeks follow-up period: weight decreased an average of 2 to −4.5 pounds (p<0, 001) and HbA1C also decreased from 9.7% to 7.8% (p<0, 001), with a consistent trend toward better outcomes after DAK, as compared to placebo. The average effect of Ongael was 0.5% (SD 2.5) decrease of HbA1C. Furthermore, seventy-five percent (41/55) of the patients reduced their HbA1C by at least 0.7% at 12 weeks. Conclusion: The observed trends in this trial suggest that poorly controlled diabetic patients improved their control of diabetes within 12 weeks when drinking DAK for at least 6 weeks. The drink DAK, in addition to the usual prevention activities of special diet and physical exercise, was followed by improvement of diabetes control (HbA1C) and decrease of blood pressure and weight. Trial registration: The study protocol was approved by the Institutional Ethical Committee and registered by international Australia and New Zealand trial registry (Request Number: 369395) Funding: Pacific Academic Institute for Research office fund, Belau Medical Clinic, The Environment, Inc, Antenna Foundation, Grandjean and Michèle Berset funds and the Weil Foundation Graphical abstract: